Kemampuan Perangkap dengan Umpan Berbasis Kelapa dalam Pengendalian Kepadatan Tikus Rumah - Ni'mah, Maftuhatun; Syakbanah, Nur Lathifah; Sulistiono, Eko; Prasidya, Denaya Andrya (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2024)
Rats are still a major problem in Indonesia, especially because of their role as rodents that carry leptospirosis and plague. Surveillance and control of rats will limit the transmission of these diseases to humans, such as installing various types of rat-trapping with appropriate bait. This study aims to determine the correlation between trap types with roasted coconut and wingko bait in controlling the density of house rats in Rancangkencono Village, Lamongan. This type of research is a quantitative quasi-experimental study that involves respondents who are not selected randomly. The research sample comprised 40 houses divided into four hamlets, using purposive sampling. Data collection was carried out for 3 days starting at 16.00-7.00 with a total of 240 traps installed, consisting of 120 live and sticky traps. The results showed that the success value of rat-trapping in Rancangkencono Village was 78.75%. There was a significant difference between live traps and sticky traps on rat density (p=0.000), with the success trap value of live trap and sticky trap being 40.83% and 116.67%, respectively. There was a significant difference between roasted coconut bait and wingko bait on rat density (p=0.001), with bait successfully eaten were 22 and 33 pieces, respectively. It concluded that the rat density level in Rancangkencono Village, Lamongan was in the high category. The most effective type of trap and bait variation in catching rats was sticky trap with wingko bait, so it can be used in controlling house rats. Keywords : rat; success trap; trap type; bait